2009
DOI: 10.1590/s1809-29502009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento de graduandos em fisioterapia na Universidade de Fortaleza sobre o Sistema Único de Saúde

Abstract: Um novo modelo de saúde pública, visando corrigir o sistema de saúde inadequado às necessidades da população, foi proposto na 8ª Conferência Nacional de Saúde em 1986. Até hoje, porém, o funcionamento do sistema único de saúde (SUS) ainda está muito distante de seus princípios básicos. Uma questão freqüente a respeito é a da capacitação de profissionais para atuar no SUS. Este estudo objetivou avaliar o conhecimento sobre o SUS dos graduandos em Fisioterapia na Universidade de Fortaleza, por meio da ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
1
3
0
9
Order By: Relevance
“…In the research, it was observed that 19% of the students wish to work exclusively in the public sector, and 78.6% wish to work both in the public and the private services. A similar result was found by Pinheiro et al 6 , once 87.5% of the students revealed the desire to work for both sectors.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the research, it was observed that 19% of the students wish to work exclusively in the public sector, and 78.6% wish to work both in the public and the private services. A similar result was found by Pinheiro et al 6 , once 87.5% of the students revealed the desire to work for both sectors.…”
Section: Discussionsupporting
confidence: 88%
“…A similar study was conducted with Physical Therapy students of Universidade de Fortaleza (CE), which also showed the good performance of students as to theoretical preparation for questions concerning origin, popular participation, doctrinaire and organizational principles of SUS 6 . This situation is explained by the analysis of the program of the Physical Therapy course, which consists of theoretical disciplines that approach the matter of collective health, public health and community physical therapy in the 4 th period, and all of the students who participated in this study had already taken such disciplines.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Acredita-se que isto reduza o interesse dos acadêmicos pela saúde pública e por estratégias de atenção primária (10,24,25) .…”
Section: Discussionunclassified